MODEL INVESTASI FUZZY UNTUK ANALISIS KELAYAKAN FINANSIAL USAHA DIVERSIFIKASI INDUSTRI BERBASIS TEBU - Sri Martini; Sukardi Sukardi; Marimin Marimin; Andes Ismaya (SOCA: Jurnal Sosial Ekonomi Pertanian, 2010)
Financial analysis is required to prevent the failure of a project when it is implemented. The obstacles and risksof the Prolect implementation that might arise should be minimized. The analysis is complex due to uncertainfuture situation. Fazzy approach is one of the methods to examine and handle this uncertainty. This research isaimed to study finzy financial feasibility indicators, to arrange fuzzy fnancial feasibility model, and to apply thismodel to bioethanol industry as a derivate of sugar cane product. Feasibility indicators of fazzy rnvestment modelstudied included NPV Fuzzy, IRR Fuzzy, and B/C Ratio Fuzzy. Raw materials cost, selling price, and interestrate made as fuzzy variables with Triangular Fuzzy Number (ffN) representation. Model feasibility informationwas categorized into four categories; unfeasible, fairly feasible, feasiSle, and very feasible. Model validation wasconducted by comparing rhe fuzzy method output with conventional method.Model verffication on bioethanol industry using fuzzy method showed this industry was feasible to be developedbased on assumption of 10 years project periods, with Rp 18.910.000.000 NPV; L.46 B/C ratio; and 253o/oIRR. Calculation using fuzzy method gave different results from conventional method calculation, however itshowed on the same trend.